'Information and Inspiration': Wangari Maathai, the Green Belt Movement and Eco-Children's Literature. Issue 1 (July 2016) - Smulders, Sharon
Abstract : Starting with seven seedlings in 1977, Wangari Maathai had, by the time of her death in 2011, become a legendary figure in the Green Belt Movement which, in its simplest terms, understands tree planting as fundamental to civic education, political advocacy, community empowerment, economic sustainability and global biodiversity. Taking Maathai's epic stature into consideration, this paper will examine how five picturebook biographies negotiate various eco-pedagogical strategies to encourage environmental awareness in children. Moreover, this paper will not only explore the verbal and visual rhetoric of tree planting but also examine how contemporary children's literature seeks to represent the third world to the first by engaging and promoting issues related to eco-literacy, indigeneity, women's rights and environmental justice.